Efektivitas Sosial Media Marketing Dalam Membangun Brand Institusi Pendidikan: Perspektif Generasi Z - Stefani Manggopa; Carolina Sumenda; Lilly Linne Kainde Anita; Deske Mandagi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to analyze generation Z's perception of the effectiveness of SMM in building brands in educational institutions, especially universities. Specifically, this study investigates the influence of SMM on four dimensions of brand gestalt, namely storyscape, sensescape, servicescape, and stakeholders. The design of this study is descriptive causal, with primary data collection through a survey of 225 samples of active students of Klabat University. Data analysis was carried out using Structural Equation Modeling (SEM) with the support of SmartPLS statistical program. The results of the analysis show that SMM has a positive and significant influence on brand trust. Furthermore, brand trust has a positive and significant influence on the four dimensions of brand gestalt, namely storyscape, sensescape, servicescape, and stakeholders. The findings provide information about the important role social media plays in building strong brand perceptions.